The Application of Six Sigma Framework (Define-Measure-Analyse-Improve-Control) to Improve Product Quality in Water Dispenser Manufacturing Company - Tannady, Hendy; Jiddan, Fauzan (Jurnal Sistim Informasi dan Teknologi, 2024)
This research aims to determine the causes of water dispenser product defects and find the main factors causing defects. This research was conducted in the form of a case study. The data used consists of quantitative data, supported by qualitative data. The analytical method used is Six Sigma, with a focus on the DMAIC method (define, measure, analyze, improve, and control) and sigma values. The population of this research is all water dispenser product equipment. Through observation, interviews and documentation techniques, this research collected data. The data processing method used is DMAIC Six Sigma, with a special focus on the Measure stage. Based on the research results, it was found that the process performance of the water dispenser product was at the level of 4.72 sigma with a DPMO value of 633,732. The most dominant defect occurs in the motor pump. Causes of defects in water dispenser products include human factors (inexperienced operators, errors in reading work instructions, unclear job holders, products not completed on time), materials (parts that do not meet standards, inspection/test equipment that does not function, CBU units that do not conform to standards), methods (products do not meet customer expectations, finished products do not meet standards, inspector operators do not master the use of measuring equipment according to regulations, customer complaints are not handled properly), and environment (hot room conditions, unstable room temperature). The most influential cause and priority for improvement is that customer complaints are not resolved or solutions are sought by the supplier.